2017
DOI: 10.7150/jbm.18949
|View full text |Cite
|
Sign up to set email alerts
|

Role of CXCL12/CXCR4-Mediated Circulating Fibrocytes in Pulmonary Fibrosis

Abstract: Pulmonary fibrosis is characterized by excessive deposition of extracellular matrix (ECM) and remodeling of the lung architecture, with clinically irreversible loss of lung function. The exact molecular and cellular mechanisms of pulmonary fibrosis are complicated. Many types of cells are involved in the pathogenic processes. The chemokine (C-X-C motif) ligand 12 (CXCL12) can attract circulating fibrocytes trafficking into lungs via chemokine (C-X-C motif) receptor 4 (CXCR4) to promote tissue repair or imperti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 78 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…Remarkably, it has been indicated recently that the homologous CXCR4 agonist CXCL12 was administered in ARDS experimental models and could produce lung protection [ 41 ]. When compared with the affinity of CXCL12, the affinity of CXCR4 was lower on lung function after isolated lung ischemia–reperfusion injury [ 42 ]. Studies have found that the overexpression of CXCR4 in MSCs can increase the chemotaxis and invasiveness of MSCs to CXCL12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, it has been indicated recently that the homologous CXCR4 agonist CXCL12 was administered in ARDS experimental models and could produce lung protection [ 41 ]. When compared with the affinity of CXCL12, the affinity of CXCR4 was lower on lung function after isolated lung ischemia–reperfusion injury [ 42 ]. Studies have found that the overexpression of CXCR4 in MSCs can increase the chemotaxis and invasiveness of MSCs to CXCL12.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can reduce the collagen differentiation and collagen deposition of fibroblasts by secreting the protein caltin-1 to maintain the stability and integrity of endothelial cells to promote tissue homeostasis [ 27 , 45 ]. However, Xie [ 42 ] et al pointed out that CXCL12 can attract many CXCR4[+] fibrocytes to gather and migrate to the lung tissues to promote tissue repair and malignant fibrosis. CXCR4 is regulated by multiple cytokines and different pathways and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrocytes secrete a variety of cytokines to augment fibrotic lesions by activating resident fibroblasts. 40 Fibrocytes are an important source of fibroblasts and myofibroblasts. In one study, circulating fibrocytes indicated a poor prognosis in IPF, 41 with circulating fibrocyte counts in the blood of patients with AE-IPF found to be elevated by up to 10-fold in comparison with the values in stable IPF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the past that SDF-1 regulates the migration of stem cells via its receptor CXCR4 and attenuates bleomycin-induced fibrosis in mice models [15]. Contrarily, there are other studies suggesting that SDF-1-dependent recruitment of CXCR4+ fibrocytes further aggravates the disease [16,17]. However, attempts were made to test CXCR4 antagonist as a potential antifibrotic agent that showed promising results in preclinical settings [18,19], but unfortunately could not be translated successfully into clinical application [20].…”
Section: Introductionmentioning
confidence: 96%